Retrobulbar hemodynamics and aqueous humor levels of endothelin-1 in exfoliation syndrome and exfoliation glaucoma - Koukoula SC (Dove Medical Press, 2018)
Stavroula C Koukoula,1,2 Andreas Katsanos,2,3 Ioannis K Tentes,4 Georgios Labiris,1,2 Vassilios P Kozobolis1,2 1Department of Ophthalmology, University Hospital of Alexandroupolis, Alexandroupolis, Greece; 2Eye Institute of Thrace, Alexandroupolis, Greece; 3Ophthalmology Department, University of Ioannina, Ioannina, Greece; 4Department of Biochemistry, Medical School, Democritus University of Thrace, Alexandroupolis, Greece Background: Endothelin-1 (ET-1) is the most potent vasoconstrictor in the body. There are reports in the literature correlating plasma levels of ET-1 and its impact on retrobulbar hemodynamics. This study evaluates aqueous humor levels of ET-1 and retrobulbar hemodynamics in patients with exfoliation syndrome (XFS) and exfoliation glaucoma (XFG). Patients and methods: Patients scheduled for cataract surgery were included. Patients were allocated to non-exfoliation non-glaucoma group (controls), XFG and XFS groups. Peak systolic velocity (PSV), end diastolic velocity, and resistivity index of the ophthalmic artery (OA), short posterior ciliary arteries, and central retinal artery (CRA) were determined preoperatively using color Doppler imaging. Aqueous humor samples obtained at the beginning of cataract surgery were analyzed with enzyme-linked immunosorbent assay. Results: Sixty-nine participants of similar age were included (controls: n=24, XFG: n=22, XFS: n=23). Multiple regression analysis showed that ET-1, OA-PSV, OA-resistivity index, CRA-PSV, and CRA-end diastolic velocity were influenced by group but not by sex or age. ET-1 for the XFG group (15.93±2.8 pg/mL) was significantly higher than for the XFS (8.92±2.7 pg/mL) and control (8.44±2.6 pg/mL) groups. The difference in ET-1 titers between the control and XFS groups was not statistically significant. All four hemodynamic parameters affected by group status significantly correlated with ET-1 levels in eyes with XFS. In eyes with XFG, two of the four hemodynamic parameters significantly correlated with ET-1 levels. In control eyes, no correlation between ET-1 and hemodynamic parameters affected by group status was detected. Conclusion: ET-1 aqueous levels in eyes with XFG were significantly higher than those of age-matched controls. Reduced blood flow and increased vascular resistivity were detected in the OA and the CRA in eyes with XFG/XFS. ET-1 levels in eyes with XFG/XFS exhibit a significant correlation with hemodynamic parameters that indicate reduced perfusion. Keywords: pseudoexfoliation, exfoliative glaucoma, color Doppler imaging